ANALISIS BIAYA TRANSPORTASI ES KRIM DI PT.XYZ - Armando Sun Angle Simbolon; Moh Dafa; Aga Purwana (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
In the distribution process a company usually has obstacles to the delivery of goods to be sent to retailers, usually the constraints occur in large transportation costs for one distribution, which results in large costs. The right method to solve this problem is Economic Scale and Economic of Distance, due to a decrease in production costs per unit in an enterprise accompanied by an increase in production volume or output. So, the larger the company, the lower the cost of production per unit of product that will be produced as well as for the more goods transported, the smaller the cost per unit I am